PROFIL GURU IDEAL DALAM NOVEL NIJUUSHI NO HITOMI KARYA TSUBOI SAKAE - Pratama, I Made (Humanis, 2016)
The title of this research is “Profile of Ideal Teacher in Nijuushi no Hitomi Novel by Tsuboi Sakae”.This research aims to find out profile of ideal teacher as reflected by Oishi Sensei character, and also Oishi Sensei’s attitude and attitude change towards the teaching profession. The theoriesused in this research are psychology literature according to Ratna, educational psychology according to Whitherington, and social psychology according to Aronson. Based on the analysis result, Oishi Sensei character of Nijuushi no Hitomi Novel reflects the ideal teacher which capable to understand the nature of students, she has the knowledge and teaching techniques, she has a positive attitude, she capable to understand the students’ personal, she give motivation to students and became of inspiration source, and she capable to perform the simple reflex activity. Oishi Sensei’s attitude and attitude change toward the teaching profession includes three components of human attitude, namely the cognitive component, affective component, and conative component. The factors that influence attitude change of Oishi Sensei character are external factors, namely school principal and her students. Oishi Sensei had decided to stop being a teacher. However, she returned to teaching after the war ended even if only as a temporary teacher.
Keywords: profile of ideal teacher, attitude and attitude change, Nijuushi no Hitomi